Optical properties of diamond films grown by MPCVD method with alternating nanodiamond injection - PEROVA, TANIA (Society of Photo-optical Instrumentation Engineers (SPIE), 2005)
Transparent polycrystalline diamond films with grain size ranging from a few tens to hundreds of nanometres were prepared on fused silica substrate by Microwave Chemical Plasma Vapour Deposition method (MPCVD). The new technique, called alternating nanodiamonds injection, was applied for substrate pretreatment. It was demonstrated that nanodiamonds injected on fused silica substrate serve as nucleation centres and make possible an increase in nucleation density to 1010 cm-2. The influence of MPCVD parameters such as methane concentration, total pressure and substrate temperature on the crystalline structure and optical properties of diamond films were investigated by using micro- Raman spectroscopy and scanning electron microscopy, transmittance and reflectance measurements in the wavelength range of 400-1000 nm. Under appropriate MPCVD parameters, diamond films with optical transmission ~70% from 650 to 1000 nm and high content of diamond phase were fabricated.
PUBLISHED
Keywords: diamond films; nucleation density; Raman spectroscopy; nanodiamond